2012
DOI: 10.1121/1.4757641
|View full text |Cite
|
Sign up to set email alerts
|

Temporary threshold shifts and recovery in a harbor porpoise (Phocoena phocoena) after octave-band noise at 4 kHz

Abstract: Safety criteria for underwater sound produced during offshore pile driving are needed to protect marine mammals. A harbor porpoise was exposed to fatiguing noise at 18 sound pressure level (SPL) and duration combinations. Its temporary hearing threshold shift (TTS) and hearing recovery were quantified with a psychoacoustic technique. Octave-band white noise centered at 4 kHz was the fatiguing stimulus at three mean received SPLs (124, 136, and 148 dB re 1 μPa) and at six durations (7.5, 15, 30, 60, 120, and 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 42 publications
6
62
1
Order By: Relevance
“…Finneran et al (Finneran et al, 2010a) have demonstrated a substantial increase in TTS with increasing exposure duration while keeping SEL constant. The same observation has been presented by Kastelein et al (Kastelein et al, 2012): bandpass fatiguing noise centered at 4 kHz resulted in higher TTS at an SPL of 124 dB re. 1 μPa than noise of the same SEL at an SPL of 136 dB re.…”
Section: Introductionsupporting
confidence: 62%
“…Finneran et al (Finneran et al, 2010a) have demonstrated a substantial increase in TTS with increasing exposure duration while keeping SEL constant. The same observation has been presented by Kastelein et al (Kastelein et al, 2012): bandpass fatiguing noise centered at 4 kHz resulted in higher TTS at an SPL of 124 dB re. 1 μPa than noise of the same SEL at an SPL of 136 dB re.…”
Section: Introductionsupporting
confidence: 62%
“…The porpoise was well trained and had participated in a number of psychoacoustic studies, including a recent study on TTS (Kastelein et al, 2012). Veterinary records of the animal showed no exposure to ototoxic medication.…”
Section: Study Animalmentioning
confidence: 99%
“…If animals remained in the impact zones, they would be exposed for weeks to noise levels known to impair harbor porpoise hearing in short-term experiments (e.g. Lucke et al 2009, Kastelein et al 2012. Alternatively, if porpoises avoided the seismic survey area and moved tens of kilometers, as documented in other areas (see above), this would force them out of their core habitat, either south of the species' range, offshore into deep waters, or into areas of low porpoise density, where the habitat is presumably sub-optimal because of reduced prey availability or other ecological factors (Fig.…”
Section: Case Studies Case 1: Harbor Porpoises Off Central Californiamentioning
confidence: 99%